Pengaruh Likuiditas dan Solvabilitas terhadap Kinerja Keuangan pada Perusahaan Sektor Healhtcare yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2020-2023 - Nur Azizah; Taat Kuspriyono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
During the period of international integration, the global economy showed significant progress. Along with technological advances brought major changes to the business sector. This resulted in the emergence of new companies in various industrial fields, thus providing a competitive advantage for the business world and increasing the level of competition between entrepreneurs. To be able to compete in the face of globalization and develop the world economy, it is important to have an effective processing strategy that can adapt efficiently and effectively to environmental changes. This step is done so that the company can continue to exist in the global world. Companies need to develop a plan to withstand changes in the business world.